Climate evolution and forcing during the last 40 ka from the oscillations in Apennine glaciers and high mountain lakes, Italy - Giraudi, C (Journal of Quaternary Science, 2017)
The results of studies carried out on the variations of glaciers and lakes in the higher Apennines during the last 40 ka are considered for correlation with some climate forcing agents, e.g. changes in insolation, variations in origin of the air masses carrying moisture and North Atlantic events, acting both at regional and hemispheric scales. The origin of air masses was assessed using the Apennine equilibrium line altitude pattern, the presence of a quartz-rich loess in the former glacial environment and the sedimentation rate of Sahara quartz in maar lakes. Temperature and humidity variations have been deduced from glacier expansions and retreats and lake oscillations. The data discussed in the paper show that variations in insolation have driven climatic changes in the Apennines for most of the considered time span, producing gradual changes that took place during periods lasting several thousand years. However, during some periods, insolation seems to have been of minor importance compared to variations in frequency and intensity of southern air currents, and to the influence of North Atlantic events. The data, as a whole, allow us to highlight the climatic evolution of the high Apennine mountains during the last 40k cal a BP. Copyright © 2017 John Wiley & Sons, Ltd.